Genetic diversity among plants of non-transgenic and transgenic versions of a single cross maize hybrid - Laserna, María Paula (2015)
Previous studies have documented that transgene introduction may alter the phenotypic expression of several traits (e.g., biomass production, grain yield). We hypothesized that genetic diversity could influence the phenotypic variation among hybrids of a same genetic background and also among plants of a hybrid. The objectives of this preliminary study were: (i) to quantify the genetic diversity between the non-transgenic (DK747) and transgenic versions (DK747MG, DK747RR and DK747MGRR) of a single-cross maize hybrid and among plants of each version, (ii) to observe the distribution of genetic diversity along the genome and (iii) to explore relationships between phenotypic variability and genetic diversity. Hybrids were cultivated at field conditions during two growing seasons and plants of each hybrid with high, intermediate and low biomass at physiological maturity were selected to perform a study of single nucleotide polymorphisms (SNP). Genetic diversity among plants of each version was greater than among versions and both sources of variation were significant (ΦST = 0.45, P < 0.01). Genetic diversity of the non-transgenic DK747 was higher than those of the transgenic versions, probably reflecting the conventional breeding history of these iso-hybrids. Similarity coefficients indicate that the most homogeneous group was that composed by plants of DK747MGRR. A Fisher's exact test together with a principal component analysis identified certain SNPs related to the contrasting plant biomass of DK747, 747MG and DK747RR. Caution should be taken with these results, because of the small sample size for SNPs study and the narrow set of tested hybrids.